2016
DOI: 10.1097/md.0000000000005018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ultrasound-guided fascia iliaca compartment block after hip hemiarthroplasty

Abstract: Background:The fascia iliaca compartment block (FICB) provides an analgesic effect in patients with femur fractures. However, the postoperative pain after hip surgery is different from that after femur fracture, because of the difference in the degree and location of tissue trauma. Whether FICB provides effective postoperative analgesia in patients undergoing total hip arthroplasty is not well understood. Moreover, there is no prospective randomized study to evaluate FICB as a postoperative analgesia in hemiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 26 publications
3
32
1
4
Order By: Relevance
“…Of the 7 articles, 1 study each was carried out in Australia, 13 China, 26 Thailand, 27 Korea, 29 Belgium, 30 Greece, 31 and Ethiopia. 4 Our present study involved 252 cases with FICB and 256 cases with NB.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 7 articles, 1 study each was carried out in Australia, 13 China, 26 Thailand, 27 Korea, 29 Belgium, 30 Greece, 31 and Ethiopia. 4 Our present study involved 252 cases with FICB and 256 cases with NB.…”
Section: Resultsmentioning
confidence: 99%
“…Bang, et al study found that FICB in hemiarthroplasty has less opioid consumption at 4, 8, and 12hours in the postoperative period, and the total fentanyl consumption during postoperative 24hours was decreased in patients with the FICB which supported our results. 13 Paut, et al noticed the presence of minimal side effects among the FICB study group that was mainly nausea and vomiting. 14 Nie, et al compared the effect of continuous FICB with fentanyl patient control analgesia in patients after hip surgeries found that 2.6 %, suffered pruritus in FICB.…”
Section: Discussionmentioning
confidence: 98%
“… 17 Bang et al also performed a prospective, randomized trial of patients who received FICB versus patient-controlled analgesia in postoperative hemiarthroplasty patients and found visual analog scales were similar in both groups; however, opioid use was significantly lower in the block group. 40 A 2002 Cochrane review demonstrated appropriately based nerve block reduced the amount of oral and parenteral analgesics postoperatively. 41 Foss et al performed a double-blinded study where 1.0% mepivacaine was injected into the fascia iliaca block versus normal saline and found a reduction in opioid consumption in the fascia iliac block cohort.…”
Section: Postoperative Pain Control With Ficbmentioning
confidence: 99%